MODEL OPTIMASI ECONOMIC ORDER QUANTITY DENGAN SISTEM PARSIAL BACKORDER DAN INCREMENTAL DISCOUNT - Nurhayati, Neri; Puspita, Nikken Prima; SRRM, Titi Udjiani (MATEMATIKA, 2017)
Economic Order Quantity model with partial backorder system and incremental discount is an integration of several model of inventory optimation, they were Economic Order Quantity optimation model, Economic Order Quantity optimation model with partial backorder system and Economic Order Quantity optimation model with incremental discount. Beside the discounts are given by supplier, in this model there were two stockout conditions, where the consumers disposed to wait until the order came and consumers did not disposed to wait until the order came.Â